High Potency of Indolyl Aryl Sulfone Nonnucleoside Inhibitors towards Drug-Resistant Human Immunodeficiency Virus Type 1 Reverse Transcriptase Mutants Is Due to Selective Targeting of Different Mechanistic Forms of the Enzyme - Cancio, Reynel (American Society for Microbiology, 2005)
Indolyl aryl sulfone (IAS) nonnucleoside inhibitors have been shown to potently inhibit the growth of wild-type and drug-resistant human immunodeficiency virus type 1 (HIV-1), but their exact mechanism of action has not been elucidated yet. Here, we describe the mechanism of inhibition of HIV-1 reverse transcriptase (RT) by selected IAS derivatives. Our results showed that, depending on the substitutions introduced in the IAS common pharmacophore, these compounds can be made selective for different enzyme-substrate complexes. Moreover, we showed that the molecular basis for this selectivity was a different association rate of the drug to a particular enzymatic form along the reaction pathway. By comparing the activities of the different compounds against wild-type RT and the nonnucleoside reverse transcriptase inhibitor-resistant mutant Lys103Asn, it was possible to hypothesize, on the basis of their mechanism of action, a rationale for the design of drugs which could overcome the steric barrier imposed by the Lys103Asn mutation.